2017
DOI: 10.1021/acs.analchem.7b03327
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free DNA Assay by Metal Stable Isotope Detection

Abstract: The interest in label-free bioassays is increasing rapidly because of their simple procedure and direct information on the interaction between the target molecule and the sensing unit. One of the major obstacles in the application of label-free biosensors is the difficulty to produce stable and reproducible optical, electric, electrochemical, or magnetic properties for the sensitive detection of the target molecules. In this work, we demonstrated a label-free DNA assay, by directly measuring the intrinsic Cu a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…A further modification of the same approach led to the development of a highly sensitive HCR based bioassay in which intrinsic Cu isotopes ( 63 Cu and 65 Cu) with the formed DNA-templated Cu-NPs were detected by ICPMS ( Figure 5(B)). [57] The method acquired a linear relation with the concentration of target DNA over the range of 20-1000 pM with a detection limit of 4 pM. This method provided the first report on the label-free DNA sensing bioassay based on metal stable isotope detection.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 94%
See 3 more Smart Citations
“…A further modification of the same approach led to the development of a highly sensitive HCR based bioassay in which intrinsic Cu isotopes ( 63 Cu and 65 Cu) with the formed DNA-templated Cu-NPs were detected by ICPMS ( Figure 5(B)). [57] The method acquired a linear relation with the concentration of target DNA over the range of 20-1000 pM with a detection limit of 4 pM. This method provided the first report on the label-free DNA sensing bioassay based on metal stable isotope detection.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 94%
“…This design showed potential in the quantitative detection of DNA for biological and medical applications. A further modification of the same approach led to the development of a highly sensitive HCR based bioassay in which intrinsic Cu isotopes ( 63 Cu and 65 Cu) with the formed DNA‐templated Cu‐NPs were detected by ICPMS (Figure (B)) . The method acquired a linear relation with the concentration of target DNA over the range of 20–1000 pM with a detection limit of 4 pM.…”
Section: The Application Of Dna‐templated Cu‐nps Sensing Of Various Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Benefiting from their excellent luminescence properties, copper nanoclusters (Cu NCs) have been successfully applied in fluorescence analysis . In this study, based on the properties of d ‐PA and copper interaction demonstrated in the treatment of Wilson's disease, we established a sensitive and selective method for determination of d ‐PA using Cu NC‐based fluorescence enhancement.…”
Section: Introductionmentioning
confidence: 99%